Is cost recovery a feasible objective for water and electricity ? the Latin American experience - Foster, Vivien 1968-; Yepes, Tito.; World Bank. (Washington, D.C. : World Bank, 2006)
"Given the relatively small segment of the population that faces genuine affordability problems in Latin America, there appears to be a promising case for using targeted subsidies to reconcile the cost recovery objective with social protection concerns. Social tariff schemes of various kinds are already widespread in Latin America, but they suffer from a number of design flaws. Increasing block tariff (IBT) structures are the most prevalent form of social tariffs in the region. These are likely to be more successful in the electricity sector than in the water sector because the correlation between consumption and income is much stronger in the case of electricity than water. Moreover, IBT structures in electricity tend to be much better designed than in the case of water, with lower fixed charges, lower subsistence blocks, and steeper gradients. A number of more sophisticated social tariff schemes are also being applied that combine consumption criteria with some form of socioeconomic screening. These are generally found to perform better than IBTs, although they also present significant room for improvement. "--World Bank web site.
Title from PDF file as viewed on 8/28/2006.
Includes bibliographical references.
Also available in print.
System requirements: Adobe Acrobat Reader.
Mode of access: World Wide Web.
Zahid
Keywords: Public utilities -- Latin America; Infrastructure (Economics) -- Latin America